CP-010 Use and effectiveness of plerixafor for haematopoietic stem cells mobilisation. (25th February 2017) - Sanchez, M; Ortgega, JM; Calvo, L; Gomez, N; Navarro, I; Abarca, C
Abstract : Background: Plerixafor is an immunostimulant used in combination with granulocyte–colony stimulating factor (G-CSF) to mobilise peripheral blood for collection and subsequent autologous transplantation in patients with lymphoma or multiple myeloma. Peripheral blood stem cell mobilisation, which is important as a source of haematopoietic stem cells for transplantation, is generally performed using G-CSF alone but is ineffective in about 15–20% of patients. Combining G-CSF with plerixafor increases the number of people who respond to the therapy and produce enough stem cells for transplantation. Purpose: To describe the use and effectiveness of plerixafor for haematopoietic stem cell transplantation recipients. Material and methods: A retrospective observational study was conducted including patients who received plerixafor between May 2011 and August 2016. The variables collected were: sex, age, diagnosis, G-CSF dose received, plerixafor dose received and CD34+ cells/kg collected. The optimal dose of CD34+ cells collected is ≥5x10 6 cells CD34+/kg, the minimum dose is ≥2x10 6 cells CD34+/kg and an insufficient dose is ≤2x10 6 cells CD34+/kg. The end point was the percentage of patients who collected at least 2x10 6 CD34+ cells/kg. Results: Plerixafor was prescribed in 14 patients, 6 women and 8 men, with an average age of 44 years. A total of 11 patients were diagnosed with lymphoma and three patients with myeloma. All had been treated previously with G-CSF alone without response. The plerixafor dose given was 0.24 mg/kg. and all had previously received G-CSF 10 µg/kg daily for 4 days prior to the first dose of plerixafor. 5 patients required 2 doses of plerixafor. This increased the cost of treatment. 2 (14%) of 14 patients had an optimal mobilisation response to treatment and ≥5x10 6 cells CD34+/kg were collected. 10 patients (72%) had a minimum mobilisation response (≥2x10 6 cells CD34+/kg). 2 patients (14%) had a suboptimal mobilisation response to treatment (≤2x10 6 cells CD34+/kg). Adverse effects were not observed. Conclusion: In general, plerixafor is an effective drug for haematopoietic progenitor cell mobilisation for autologous transplantation; in 72% of patients, at least 2×10 6 CD34+ cells/kg were collected. References and/or acknowledgements: Mozobil: EPAR-Summary for the public. EMA. No conflict of interest